<h2>JK = 18m</h2><h2>_______________</h2>
<u>Step-by-step explanation:</u>
ΔJLK = ΔNLM ( <em>v</em><em>e</em><em>r</em><em>t</em><em>i</em><em>c</em><em>a</em><em>l</em><em>l</em><em>y</em><em> </em><em>o</em><em>p</em><em>p</em><em>o</em><em>s</em><em>i</em><em>t</em><em>e</em><em> </em>Δ)
ΔJKL = ΔNML ( <em>e</em><em>a</em><em>c</em><em>h</em><em> </em><em>9</em><em>0</em><em>°</em><em> </em><em>)</em>
so,
triangle JKL = triangle NML (<em>b</em><em>y</em><em> </em><em>A</em><em>A</em><em> </em><em>s</em><em>i</em><em>m</em><em>i</em><em>l</em><em>a</em><em>r</em><em>i</em><em>t</em><em>y</em><em>)</em>
JK / KL = NM / ML
JK / 21m = 42m / 49m
JK = 42 × 21 ÷ 49
JK = 18m
<h2>_______________</h2><h2>FOLLOW ME</h2>
Answer:
Answer to Given the functions: 1 f (x)=4x g(x)= | x-3 1 h(x)= x+6 Evaluate the function (f-g)(x) for x=-6. (4-8)(-6) is DO Undefine...
Answer:
Step-by-step explanation:
Here, following formula will be used
(a+b)²= a²+b²+2ab
question
5(3a + b)² +6 (3a +b) - 8
=> we will take out 3 as common number to make the term (3a+b) to fit formula requirement
=> 5x3 (a+b/3)²+6(3a+b)-8
=> 15(a²+b²/9+2xaxb/3)+18a+6b-8
here, we have expanded the formula
=> 15a²+15b²/9+15x2ab/3+18a+6b-8
=> 15a²+5b²/3+10ab+18a+6b-8